Young children's experiences of support when fearful during treatment for acute lymphoblastic leukaemia-A longitudinal interview study - Ingela Leibring; Agneta Anderzén‐Carlsson (Wiley, 2022)
Abstract Aim and objectives To describe young children's experiences of valuable support in managing their fears about treatment for acute lymphoblastic leukaemia. The focus was specifically on support from parents and healthcare professionals. Design The study had a qualitative descriptive longitudinal design. Methods The study analysed 35 interviews with 13 children at three different times during their treatment period. Data were analysed using a matrix‐based method. The Consolidated criteria for reporting qualitative research (COREQ) guidelines have been followed. Results Parents and healthcare professionals provide important support to children undergoing treatment for acute lymphoblastic leukaemia, although their roles differ. Children valued their parents' closeness and advocacy, being able to participate in their own care, and being given pain relief during procedures known to create pain. Valued support from healthcare professionals changed over time, from providing information and showing the tools that would be used in procedures, to paying attention to the child's needs and desires. It was more important for children to be able to choose between different alternatives in medical procedures than deciding on major treatment issues.